Optimal dispatch of a coal-fired power plant with integrated thermal energy storage - Eren Çam (Institute of Energy Economics at the University of Cologne (EWI), 2020)
As the share of intermittent renewable electricity generation increases, the remaining fleet of conventionalpower plants will have to operate with higher flexibility. One of the methods to increase power plantflexibility is to integrate a thermal energy storage (TES) into the water-steam cycle of the plant. TES canprovide flexibility and achieve profits by engaging in energy arbitrage on the spot markets and by providingadditional power on the control power markets. This paper considers a reference coal-fired power plant withan integrated TES system for the year 2019 in Germany. Optimal dispatch for profit maximisation withTES is simulated on the hourly day-ahead and quarter-hourly continuous intraday markets as well as on themarkets for primary (PRL) and secondary (SRL) control power. Analysing the effects of TES round-tripefficiency and storage capacity on dispatch and the profits, I find that smaller TES systems with up toone hour of storage capacity can achieve substantial profits on the PRL market while also realising profitsfrom energy arbitrage on the continuous intraday market. Higher TES round-trip efficiencies can help TESachieve significant profits also on the day-ahead market. The analysis shows that a storage capacity of 2-3hours is enough to realise most of the energy arbitrage potential, while larger storage capacities can greatlyincrease TES profits on the SRL market. Small TES systems are found to increase the full load hours ofthe plant marginally. However, the increase becomes significant with larger storage capacities and can leadto higher CO2emissions for the individual plant.
Keywords: Q40; Q49; 330; coal-fired power plant; flexibility; thermal energy storage; energy arbitrage